Finding identity without discrimination: the plight of Arab American adolescents. Issue 5 (2nd September 2016) - Tabbah, Rhonda; Wheaton, Joe E.; Miranda, Antoinette Halsell
Abstract : This study investigated the relationship between self-reported discrimination and ethnic identity among 61 Arab American adolescents between the ages of 12 and 18 years. Participants completed the Multigroup Ethnic Identity Measure (MEIM) to obtain an assessment of their ethnic identities. Additionally, the lead author developed a questionnaire asking participants to self-report if either they or another Arab student they knew had been 'treated badly or differently because of their ethnicity'. Consistent with the rejection-identification model, respondents who had reported experiencing discrimination, knowing of others who had experienced discrimination, or both had higher ethnic identity scores than those who had not, although the only significant difference was found between the group that experienced both types of discrimination and the non-discrimination group. Implications of these results are discussed as well as directions for future research.